Single‐unit transfusions in the obstetric setting: a qualitative study. Issue 7 (5th April 2016) - Mayson, Eleni; Shand, Antonia W.; Ford, Jane B.
Abstract : BACKGROUND: The rate of obstetric blood transfusion is increasing, and there is hospital variation in its use. Recent Australian guidelines recommend a restrictive transfusion strategy in maternity patients who are not actively bleeding and advocate single‐unit red blood cell (RBC) transfusions followed by clinical reassessment to determine the need for further transfusion. STUDY DESIGN AND METHODS: The aim of this study was to identify factors influencing single RBC unit use when initiating transfusion in a postpartum woman with noncritical bleeding. A qualitative research study using semistructured interviews was conducted. Nine maternity hospitals were chosen to cover a range of clinical settings and obstetric transfusion rates in Australia. Interviews were conducted with the key decision makers in obstetric blood transfusion. Interviews were transcribed and coded, and themes were developed. RESULTS: One hundred twenty‐five interviews were conducted, including 61 doctors' interviews among obstetric (n = 42) and hematology (n = 19) staff. Most doctors (54%) interviewed would initiate transfusion with 2 RBC units; and, of those who started with single‐unit transfusions, most (63%) had practiced obstetrics for less than 5 years. Clinician and external factors influenced decision making. Important clinician factors included perceived utility or clinical need and education/experience. External factors included influence of colleagues, clinical context, availability of RBC units, and regulation mechanisms. CONCLUSION: The decision to use single‐unit RBC transfusion varied between and within hospitals. Efforts to reduce exposure to blood in the obstetric setting via the number of units transfused may need to target perceptions regarding the utility of single units and lack of experience with this approach.